Pattern of computerized tomography findings of the brain in cerebrovascular accidents - Shrestha, Elina; Thapa, Narayan Bikram; Rajbhandari, SBS (Nepal Journal of Medical Sciences, 2020)
Introduction: Semi-industrialized countries like Nepal have high mortality and disability rates due to cerebrovascular accident, representing for more than 80% of all stroke deaths globally. Stroke is the most common neurological disorder requiring prolonged hospital stay. Aims of our study was to evaluate the role of computerized tomography in evaluation of cerebrovascular accident by differentiating ischemia from hemorrhage and proper identification of negative cases. Methods: A descriptive cross sectional study of total 155 patients, clinically diagnosed as stroke, referred to our department of radiology for computerised tomography evaluation during six month period, were enrolled into study. The clinical information, proper history, computerised tomography findings were properly documented and analysed in SPSS version 20 software. Results: Out of total 155 patients, 85 cases (55 %) were males and 70 cases (45 %) were females with male: female ratio of 1.2:1. The mean age of the patients was 63±15 years. There was significant correlation between clinical with neuroradiological findings as evidenced by p value of 0.000. Sensitivity, specificity, positive predictive value, negative predictive value of clinical findings when correlated to CT in diagnosing ischemic infarction were 84.3%, 67.3%, 82.6%, 70%. Similarly, sensitivity, specificity, positive predictive value, negative predictive value in diagnosing hemorrhagic infarction were 67.3%, 84.3%, 70%, 82.6% respectively. Conclusions: Computerised tomography is the first line reliable imaging modality for diagnosis, management of cerebrovascular accident and exclusion of stroke mimicker lesions. Education regarding prevention and control of modifiable risk factors can minimize the incidence of stroke.